Dampak Erupsi Gunung Sinabung Terhadap Sifat Kimia Tanah Di Kabupaten Karo - Ceriati Magdalena Simanjuntak; Deni Elfiati; Delvian Delvian (Peronema Forestry Science Journal, 2015)
This study aims to determine the impact of the eruption of Mount Sinabung on soil chemical properties in Karo. This study is exploratory in which the comparison between forest land that is not affected by the eruption (control) was taken from the village Kutagugung and forest land affected by the eruption taken from the village Sukanalu. Soil samples exposed to the eruption consisted of two samples that volcanic ash with a depth of 0-5 cm and mixed with volcanic ash soil to a depth of 5- 20 cm, while for the control of soil samples consisted of a sample of the soil to a depth of 0-20 cm. Tests conducted on soil chemical properties BPTP North Sumatra and Central Laboratory of the Faculty of Agriculture, University of North Sumatra. Results showed the soil to a depth of 5-20 cm eruption contains C-Organic, CEC, available P, total P, and S with the criteria of moderate to very high, while the volcanic ash with a depth of 0-5 cm and control soil with a depth of 0 -20 cm contains the C-Organic, CEC, N, available P, total P, K, Ca, Mg and S with the criteria of very low to very high.Keyword: volcanic eruption, Sinabung, soil chemistry, soil depth.